Production of Glucose from Banana Trunk: Optimization Studies - Wan Zaireen Shafinaz Halim (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Banana trunk (BT) is one example of non-wood fibers and usually discarded as an agricultural waste from banana plantation in Malaysia. It consists of cellulose (53.45 %), hemicelluloses (28.56 %) and lignin (15.42 %). There are mainly two processing method involved in the conversion: pretreatment and enzymatic hydrolysis of cellulose in the BT to produce glucose. Pretreatment of BT to remove lignin and hemicellulose can significantly enhance the hydrolysis process. Through an enzymatic hydrolysis process, the BT fibers can be converted into glucose. In this research, the conversion of cellulose to glucose with the help of cellulase enzyme was carried out. Response Surface Methodology (RSM) based on the Central Composite Design (CCD) was used to evaluate the interactive effects of hydrolysis, of temperature (30-45 oC), enzyme concentration (7.1-16.9 % (v/w)) and reaction time (3-15 hrs), on the yield of glucose. The optimum conditions derived via RSM were temperature 44.79 oC, enzyme concentration 12.39 % (v/w) and reaction time 14.66 hrs. As a result, the higher yield of glucose concentration from the experimental was found to be 69.80 g/L under optimum condition. A model adequacy was very satisfactory as coefficient determination was 0.971.